The real origins of the European crisis - Bogomazova, Katerina (My University, 2014)
Financial crises are a recurring event in the global macroeconomic scenario. Kindleberger and Fratianni (2008) have counted today 1622. However, with the exception of that of '29, all others have been united from having invested exclusively in developing countries.
Keywords: European crisis; macroeconomics; financial crisis; Європейська криза; макроекономіка; фінансові кризи; Финансовые кризисы; макроэкономика; Европейский кризис